THE INFLUENCE OF THE NUMBER OF FOREIGN TOURISTS AND FOREIGN DEBT TO FOREIGN EXCHANGE RESERVES IN INDONESIA - Anggia Murni; Umaruddin Usman; Jariah Abubakar; Mutia Rahmah (Journal of Malikussaleh Public Economics, 2021)
This study examines the effect of the number of foreign tourists and foreign debt on foreign exchange reserves in Indonesia. This study uses secondary data from 2005 to 2019. Data are analyzed by using multiple linear regression (Ordinary Least Squares). The result showed that the foreign tourists and foreign debt do not influence foreign exchange reserves. Simultaneously, the number of foreign tourists and foreign debt affected the foreign exchange reserves in Indonesia. The coefficient of determination (R2) was 0.839184, which indicates that the influence of the number of foreign tourists and foreign debt on foreign exchange reserves was 0.839184 or 83.91%, and the remaining 16.09% was influenced by other variables outside of this study.